MANAJEMEN LEMBAGA PENDIDIKAN ISLAM NON FORMAL “SATU ATAP” AL HIDAYAH JURANGGUNTING ARGOMULYO KOTA SALATIGA - Nugroho, Puspo (Pascasarjana IAIN Kudus, 2019)
Aims of this study is to reveal how the implementation of management of non-formal Islamic education institutions, supporting and inhibiting factors and steps taken in the framework of developing institutional management. The locus of this study was Al Hidayah One Roof Non-formal Islamic Education Institution in Ledok, Argomulyo Sub-District, Salatiga City. In the process, this study used a qualitative approach using the snowball sampling technique. Data analysis uses the Miles & Huberman Interactive Analysis Model which includes activities: (1) data reduction, (2) data presentation, and (3) drawing conclusions and verification. The results obtained show that management is managed by the chairman and secretary, treasurer and head of each institution. The implementation of managerial functions has not been fully implemented. The main constraints include the lack of funding support, the lack of consistent attention to mosque takmir, the weakening of community support and the transfer of management status from singgel to family which has an impact on changes in work focus, domicile, and family factors. Some of the steps taken include conducting organizational restructuring and formulating a funding arrangement plan, procuring new human resources through regeneration and compiling administrative governance.Keywords: Management. Islamic Education Institutions, Non-formal, One-stop